Introduction of public administration as an institutional social and economic development management systems of rural areas in Ukraine - Orlaty , Mykhailo; Shlapak , Ihor; Maksymchuk , Svyatoslav (Theory and Practice of Public Administration, 2019)
The peculiarities of public management of socio-economic development of rural territories are considered. The mechanisms of creation of prerequisites for further development of rural territories are analyzed. The system of factors of socio-economic development of rural territories, which determine the conditions and potential opportunities for socio-economic development of rural territories, is considered. The methodical approaches to the formation of a passport of the united territorial community are revealed.The main reasons for the decline of rural areas are found out is the weakness of the rural communities and self-government bodies; lack of initiative and readiness of citizens to solve local problems by their own forces, mutual trust and power structures; insufficient development of the system of public organizations. Therefore, current problems will include improvement of the legal principles of local self-government, as well as tax legislation and intergovernmental relations in the direction of strengthening the financial basis of self-government; introduction of a system of training and raising the level of qualification of employees of local self-government bodies, activists (leaders) and managers of public organizations and co-operative formations; Further development of the system of advisory activity in the countryside; support for associations created by communities (citizens) in order to solve specific problems for improving their living conditions.Improvement of the activities of local self-government bodies of Ukraine as an effective tool of public administration in socio-economic development makes it possible to identify the contiguity advantages of territoriality, the level of population satisfaction with the quality of services provided, as well as the levelof trust of citizens to the authorities. A prerequisite for ensuring the formation of capable territorial customs in Ukraine is the completion of the administrative-territorial reform, which is connected with the transformation of the institutions of state power, the development of local self-regulation, the creation the decentralized system of redistribution of budget funds, as well as the introduction of the reform of the territorial system. In this context, the definition of the jurisdiction of each rural community, the delimitation of the land of government and communal property, etc., is of particular importance.